HUBUNGAN ANTARA POLA TIDUR DAN KEBIASAAN MAKAN JUNK FOOD DENGAN KEJADIAN OBESITAS PADA MAHASISWA UNIVERSITAS MALAHAYATI TAHUN 2019 - Tanti Kristiana; Dessy Hermawan; Upik Febriani; Achmad Farich (HUMAN CARE JOURNAL, 2020)
Obesity is a serious illness that can cause emotional and social problems. The things that cause obesity include sleep patterns, and also patterns of consumption, including consumption of junk food among teenagers.This study aimed to determine the relationship of sleep patterns and Junk food eating habits with the incidence of obesity in students at Malahayati University in 2019. The type of research used was observational quantitative research with a case control approach. The sample in this study is the medical students of the University of Malahayati Bandar Lampung in 2017 consisting of 30 people who are not obese and 30 people who are obese. Data obtained through filling questionnaires and microtoise scales. The data analysis technique to test the hypothesis is the chi square statistical test. From the results of the study showed the frequency of sleep patterns with the most obesity events in the less category (43.3%), the frequency of junk food eating habits with the most obesity events in the frequent and always categories (38.4%), there was a significant relationship between sleep patterns and the incidence of obesity with a p value of 0,000 (<α0.05) and there is a significant relationship between junk food eating habits with the incidence of obesity with a p value of 0,000 (<α0.05). Students with obesity consume junk food more often and obese students also have less sleep patterns than non obese students.